The Role of Public Administration Ethics in Realizing Clean and Transparent Governance - Syadiyah, Kholifatus; Putri, Salsabilla Azzahra Niesma; Hayat, Hayat (Jurnal Ilmu Administrasi Negara (JUAN), 2024)
Public administration ethics plays a crucial role in realizing clean and transparent governance. In the context of increasing global demands for honest, just, and transparent government actions, public administration ethics ensures that government officials act with integrity, professionalism, and social responsibility. The research aims to analyze the significance of these ethics in promoting governance that is free from corruption, collusion, and nepotism (KKN), and how its application can improve public trust and the quality of services. A qualitative, descriptive research methodology, primarily utilizing a literature review, was employed to explore the role of ethical principles, such as honesty, fairness, openness, and professionalism, in the public administration process. The results of this research indicate that while ethics are integral to fostering a clean government, challenges such as a deeply rooted culture of corruption, ineffective monitoring systems, and lack of public participation hinder their full implementation. Furthermore, the study highlights the importance of transparent decision-making, public participation, and accountability in reinforcing these ethical standards. The research concludes that strengthening public administration ethics, alongside enhancing transparency and citizen engagement, is essential for ensuring the effectiveness, fairness, and trustworthiness of public governance. Consequently, it provides recommendations for governmental reform to enhance ethical practices, improve public service delivery, and foster a more accountable and transparent system.